2011
DOI: 10.3892/or.2011.1189
|View full text |Cite
|
Sign up to set email alerts
|

Gambogic acid inhibits the growth of osteosarcoma cells in vitro by inducing apoptosis and cell cycle arrest

Abstract: Abstract. the natural product gambogic acid (gA) has been demonstrated to be a promising chemotherapeutic drug for some cancers because of its ability to induce apoptosis and cell cycle arrest. Until now, no studies have looked at the role of gA in osteosarcoma. In this study, we observed the effects of gA on the growth and apoptosis of osteosarcoma cells in vitro. We found that gA treatment inhibits the proliferation of osteosarcoma cells by inducing cell cycle arrest. Moreover, we found that gA induces apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Resistance to L-OHP remains one of the major obstacles in chemotherapy for CRC, and it is essential to identify novel drugs to overcome or reverse L-OHP resistance. GA is a traditional Chinese medicine with multi-target anticancer effects, including the inhibition of proliferation ( 20 ), induction of apoptosis ( 21 ), cell cycle arrest ( 22 ), and inhibition of angiogenesis ( 23 ), invasion and metastasis ( 24 ). GA was also identified to exhibit inhibitory effects on resistance to anticancer drugs in CRC ( 12 ), breast ( 13 ), ovarian ( 14 ), gastric ( 15 ) and human epithelial cancer ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to L-OHP remains one of the major obstacles in chemotherapy for CRC, and it is essential to identify novel drugs to overcome or reverse L-OHP resistance. GA is a traditional Chinese medicine with multi-target anticancer effects, including the inhibition of proliferation ( 20 ), induction of apoptosis ( 21 ), cell cycle arrest ( 22 ), and inhibition of angiogenesis ( 23 ), invasion and metastasis ( 24 ). GA was also identified to exhibit inhibitory effects on resistance to anticancer drugs in CRC ( 12 ), breast ( 13 ), ovarian ( 14 ), gastric ( 15 ) and human epithelial cancer ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a number of previous reports, GA was found to induce apoptosis in tumor cells ( 19 , 20 ). However, in the present study, no effect of GA on caspase-3, 8 and 9 activities was identified in the NCI-H1993 xenograft model.…”
Section: Discussionmentioning
confidence: 88%
“…CDK and cyclin family proteins regulated cell cycle progress via transporting nutrients and transducing growth factors into cells. CDK4/6 related to Cyclin D1 was essential for regulating G1, 24 and they were inhibited by p16. Cyclin E1 combined with CDK2 induced cell cycle in the late G1 stage, and CDK2/Cyclin E1 complex was inhibited by p21 (tumor suppressor gene).…”
Section: Discussionmentioning
confidence: 99%